UPGRADING STRUCTURAL AND FUNCTIONAL SUPPORT FOR PERSONNEL MANAGEMENT SERVICE OF PUBLIC AUTHORITIES AS THEIR ORGANIZATIONAL DEVELOPMENT PREREQUISITE - Naboka , L. (Theory and Practice of Public Administration, 2020)
The paper is devoted to the issues of creating conditions for organizational development of public authorities, which is topical in the context of the public administrative system reform and formation of the modern public service. A general review of scientific literature proves that organizational development is based on a system of planned changes, aiming to improve the overall effectiveness of organization of a public authority’s work due to revision of values, improvement of organizational culture, organizational climate, organizational behavior, and organizational interaction. Resolving these issues is a new function of personnel management services in public authorities of Ukraine, which encourages upgrading of their structural and functional support. The paper proposes a new approach to arrangement of the structure of the personnel management service of a public authority, which is based on defining the goals of organizational development of the entire public authority and its service, the strategy, complex elaboration of the needs, interests, values, motives of personnel and customers, respective specification of functions, determining their scope, complexity, labor intensity, coordination, compliance with goals and tasks of organizational development. A model of the new structure of personnel management service was substantiated; the model presupposes an obligatory introduction of units (experts) specializing in organizational development and management of staff potential as basic units researching the condition of public authorities, outlining the vectors of organizational changes and ensuring their implementation, monitoring quality and effectiveness, organization of preemptive training of competences and traits of staff members, as well as forming a psychological follow-up unit for personnel для збереження psycho-physiological and psycho-emotional health of employees.